Impact of surgical treatment of pectus carinatum on cardiopulmonary function: a prospective study. (19th November 2020) - Del Frari, Barbara; Sigl, Stephan; Schwabegger, Anton H; Blank, Cornelia; Morawetz, David; Gassner, Eva; Schobersberger, Wolfgang
Abstract: OBJECTIVES: The frequency of sternochondroplasty in cases of pectus carinatum (PC) has increased due to greater surgeon experience and modified surgical techniques. PC deformity does not usually cause cardiopulmonary malfunction or impairment. However, whether cardiopulmonary function changes after surgical repair remains a matter of controversy. The aim of our prospective study was to determine if surgery changes preoperative cardiopulmonary function. METHODS: Nineteen patients (16 males, 3 females) were enrolled in a prospective, open-label, single-arm, single-centre clinical trial (Impact of Surgical Treatments of Thoracic Deformation on Cardiopulmonary Function) (NCT02163265) between July 2013 and January 2017. All patients underwent PC repair via a modified Ravitch procedure and wore a lightweight, patient-controlled chest brace for 8 weeks postoperatively (the Innsbruck protocol). The average follow-up surgical examination was 8.3 months after surgery. In all enrolled patients, before surgery and not before 6 months postoperatively chest X-ray, 3-dimensional volume-rendered computed tomography thorax imaging, cardiopulmonary function tests with stepwise cycle spiroergometry (sitting and supine position) and Doppler echocardiography were performed; questionnaires about daily physical activity were also completed. RESULTS: Fourteen patients (aged 16.3 ± 2.6 years at study entry) completed the study. Changes in submaximal and peak power output were not detected during sitting, or when in the supine position. Also, no clinically relevant postoperative changes in spirometry or echocardiography were noted. CONCLUSIONS: Our findings confirm that surgical correction of PC does not impair cardiopulmonary function at rest or during physical exercise. Clinical registration number: clinicaltrials.gov NCT02163265. Abstract : Pectus carinatum (PC), or keel chest deformity, refers to protrusion of the sternum possibly due to the overgrowth of costal cartilages and the adjacent ribs, and/or asymmetric cartilages [1–4].